Clinical characteristics and risk factors associated with ICU-acquired infections in sepsis: A retrospective cohort study - He, Yajun; Xu, Jiqian; Shang, Xiaopu; Fang, Xiangzhi; Gao, Chenggang; Sun, Deyi; Yao, Lu; Zhou, Ting; Pan, Shangwen; Zou, Xiaojing; Shu, Huaqing; Yang, Xiaobo; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Intensive care unit (ICU)-acquired infection is a common cause of poor prognosis of sepsis in ICU. However, sepsis-associated ICU-acquired infections have not been fully characterized. The study aims to assess the risk factors and develop a model that predict the risk of ICU-acquired infections in patients with sepsis. Methods: We retrieved data from the Medical Information Mart for Intensive Care (MIMIC) IV database. Patients were randomly divided into training and validation cohorts at a 7:3 ratio. A multivariable logistic regression model was used to identify independent risk factors that could predict ICU-acquired infection. And we assessed its discrimination and calibration abilities, and compare them with classical score systems. Results: Of 16808 included septic patients, 2871(17.1%) developed ICU-acquired infection, these patients with ICU-acquired infection had a 17.7% ICU mortality and 31.8% in-hospital mortality, and showed a continued rise in mortality from 28 to 100 days after ICU admission. The classical SIRS,SOFA,OASIS,SAPS II,LODS,CCI,and APS III scores were associated with ICU-acquired infection, and the cerebrovascular insufficiency, gram-negative bacteria, surgical ICU, tracheostomy, central venous catheter, urinary catheter, mechanical ventilation, RBC transfusion, and anticoagulant therapy were independent predictors of developing ICU-acquired infection in septic patients. The nomogram on the basis of these independent predictors showed good calibration and discrimination in both the derivation (AUROC 0.737, 95% CI 0.725-0.749) and validation (AUROC 0.751, 95% CI 0.734-0.769) populations, and was superior to that of SIRS,SOFA,OASIS,SAPS II,LODS,CCI,and APS III models. Conclusions: ICU-acquired infections increase the likelihood of septic mortality. The individualized prognostic model on the basis of the nomogram could accurately predict ICU-acquired infection and optimize management or tailored therapy.